COMPARISON OF EFFICACY AND SAFETY BETWEEN GABAPENTIN AND AMITRIPTYLINE IN PATIENTS WITH DIABETIC PERIPHERAL NEUROPATHY PAIN - Dr. Somasekhar Reddy; Dr. K. Jyoshna; Dr. Geetha Soren; Dr. K. Dhishan Sai (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
INTRODUCTION: The most disturbing sign of diabetic peripheral neuropathy is pain. Of patients with diabetes mellitus, almost thirty to fifty percent develop peripheral neuropathies. Most often occurring kind is distal symmetric sensorimotor polyneuropathy (DSPN). Two most often used medications in pain related with this disorder are amitriptyline and gabapentin. This study was conducted to compare the effectiveness and safety between Gabapentin and Amitriptyline in patients with painful diabetic peripheral neuropathy.MATERIALS AND METHODS: This study was a randomized, open-label, comparative study done over a duration of six months. Sixty patients with diabetic polyneuropathic pain were randomly assigned to two groups. Group A was administered oral Amitriptyline, whereas Group B was given oral Gabapentin for a period of 12 weeks. The patients had examination four times during the study duration. Following the baseline appointment, patients were instructed to return for following sessions at four-week intervals up to twelve weeks. Efficacy was assessed with an 11-point numeric pain rating scale and the MNSI score and adverse consequences were documented.RESULTS: The study comprised a total of 60 patients, with 30 individuals assigned to each group (Amitriptyline group and gabapentin group). The mean age of patients was 62.11 ± 3.47 in Group A and 63.46 ± 4.90 in Group B. Group A included 21 males and 9 females, whereas Group B consisted of 20 males and 10 females. The mean decrease in NPRS scores was significant between the two groups, with a greater reduction in pain seen in the Gabapentin group compared to the Amitriptyline group. The reduction in the mean MNSI (H/O) score was significant across the two groups, with a greater decrease seen in the Gabapentin group compared to the Amitriptyline group. A greater incidence of adverse events was found in the amitriptyline group compared to the gabapentin group.CONCLUSION: Both therapy groups offered clinically significant pain reduction with manageable side effects. However, gabapentin produced much more pain alleviation than amitriptyline, and gabapentin has a lower rate of side effects. Hence It may be established that gabapentin is safer and more effective than amitriptyline in individuals with painful diabetic peripheral neuropathy.